Improving Mathematic Communications Skill by Using Mathematic Realistic Setting Cooperative Learning with Student Teams Achievement Divisions (STAD) type - Tri Novita Irawati (Universitas Islam Jember, 2017)
Mathematical communication of students is the ability of students to communicate both orally and in writing in the process of learning mathematics. The ability of students' mathematical communication can increase if there is a change in learning one of them through application of Realistic Mathematics learning with STAD Type Cooperative Setting. This type of research is a classroom action research. Data analysis is done qualitatively and quantitatively to the ability of oral and written communication of students. Based on the results of analysis on the cycle I and II students' communication skills in cycle I and cycle II has increased. Student's oral communication ability in cycle I got the average score of 9.17 with the category of